Role of motivation in artistic gymnastics by results of a questionnaire based international surveyre - Munkácsi, I.; Kalmár, Z.; Hamar, P.; Katona, Z.; Dancs, H. (Journal of Human Sport & Exercise, 2012)
The hardest part of coaching work is the psychological preparation of athletes and gymnasts, where the aim is to achieve higher performance. Motivation - as the driving force of our actions - has an increased role in preparing the gymnasts, as during trainings they have to solve more complicated, more difficult tasks than in their everyday lives. A strong motivational driving force is essential to perform the high level gymnastic exercises and to practice them daily. In our inquiry we wanted to find out how much the questioned 152 foreign gymnastics coaches find motivation important and improvable. It was also a question if it is necessary to develop motivation in order to reach new aims or if the genetic level that was brought along is enough. Our results show that it is necessary to develop and reinforce motivation continuously to reach higher performances. Use of educational methods have important roles in doing so, which help to determine the long term and short term main goals and sub-aims - as a motivation.